Advances in accounting education teaching and curriculum innovations. Vol. 2 - Schwartz, Bill N.; Ketz, J. Edward (Emerald, 2000)
Advances in Accounting Education is a refereed, academic research annual whose purpose is to meet the needs of individuals interested in the ways to improve their classroom instruction. Major changes are occurring in accounting education as a result of recommendations from the Accounting Education Change Commission, the American Institute of CPAs, the Institute of Management Accountants and the American Assembly of Collegiate Schools of Business (the accrediting agency) and the new 150-Hour Requirement. We publish thoughtful, well-developed articles that are readable, relevant and reliable. Articles may be either empirical and non-empirical. They emphasize pedagogy, i.e., explaining how teaching methods or curricula/programs can be improved.
Keywords: Accounting -- Study and teaching.; elektronické knihy; electronic books